Beyond the Critique of Soteriological Individualism: Relationality and Social Cognition. (15th February 2021) - Zahl, Simeon
Abstract: This article examines an influential conceptual trope in theology and biblical studies: the distinction between 'individualistic' and 'communal' orientations as a typology for distinguishing soteriological frameworks. This distinction has been widely deployed in Paul studies, in particular, where for decades it has been invoked in order to illuminate problems with traditional Protestant soteriologies. The present article clarifies and extends recent critiques of the 'individualism vs. communalism' trope by drawing on conceptual tools from the fields of social cognition and social emotion. It argues that in appealing to the 'individualism vs. communalism' trope Paul scholars have often been operating with unarticulated assumptions about the shaping effects of soteriological frameworks on Christian experience that are subject to analysis and critique. After identifying four such assumptions, conceptual tools psychologists have developed for understanding the experience of social relation between human and human‐like agents are explicated. It is argued that these psychological resources can augment and extend recent suggestions by Susan Eastman, Volker Rabens, and others that individuality and relationality are mutually entangled rather than opposed in Paul. Finally, it is suggested that analyzing Paul's soteriology through the lens of relational experience and social emotion can open up new hermeneutical vistas for both theologians and biblical scholars.